The Prevalence of the Phenomenon of Competitive Behavior among Football Players in the Governorates of Gaza Strip - Ramzy Jaber (My University, 2010)
The study aimed to identify the prevalence of the phenomenon of competitive behavior among football players in the governorates of the Gaza Strip, according to the following variables (level - status) and to achieve this study was conducted on a sample of (140) players from the league players and the first Palestinian excellent football equivalent (28 %) of the community of the original study (500) player, and to collect data and achieving the objectives of the study was the use of the descriptive approach, and test the competitive behavior of the design Dothei Harris Harris (1984) On the Arabization of Mohammed Alawi (1998) and the results showed that: - The prevalence of the phenomenon of competitive behavior among football players in the governorates of the Gaza Strip, where the medium the percentage of response to have to (66.1%). No statistically significant differences in the degree of prevalence of the phenomenon of competitive behavior among football players due to a variable degree (excellent, I). There were no statistically significant differences in the degree of prevalence of the phenomenon of competitive behavior among football players due to the changing status (attack, defense).

هدفت الدراسة إلى التعرف إلى مدى شيوع ظاهرة السلوك التنافسي لدى لاعبي كرة القدم في محافظات قطاع غزة تبعا للمتغيرات الآتية (الدرجة – المركز) ولتحقيق ذلك أجريت الدراسة على عينة قوامها (140) لاعبا من لاعبي الدوري الفلسطيني الممتاز والأول لكرة القدم أي ما نسبته (28 %) من مجتمع الدراسة الأصلي والبالغ (500) لاعب ، ولجمع بيانات الدراسة وتحقيق أهدافها تم استخدام المنهج الوصفي، واختبار السلوك التنافسي من تصميم دوثي هاريس Harris (1984) ومن تعريب محمد علاوي (1998) وأظهرت نتائج الدراسة أن درجة شيوع ظاهرة السلوك التنافسي لدى لاعبي كرة القدم في محافظات قطاع غزة جاءت متوسطة حيث وصلت النسبة المئوية للاستجابة لديهم إلى (66.1%). لا توجد فروق ذات دلالة إحصائية في درجة شيوع ظاهرة السلوك التنافسي لدى لاعبي كرة القدم تعزى لمتغير الدرجة (الممتازة، الأولى). ولا توجد فروق ذات دلالة إحصائية في درجة شيوع ظاهرة السلوك التنافسي لدى لاعبي كرة القدم تعزى لمتغير المركز (هجوم، دفاع).
مدى شيوع ظاهرة السلوك التنافسي لدى لاعبي كرة القدم في محافظات قطاع غزة